Etude dendroécologique du pin pignon (Pinus pinea L.) dans la forêt d’Akboub Mostaganem. - BENICHOU, Hafsa (My University, 2017)
The purpose of dendroecology is to study spatiotemporal relationships between woody plants and their habitats. The current work has been undertaken to study the radial growth of pinion pine in relation to climatic conditions in the Mostaganem area. Pinus pinine (Pinus pinea L.) has been introduced in North Africa for a long time because of the use of its seed in food traditions. Growth was assessed on a sample of 12 trees belonging to the Akboub forest. Measurements were made on the rings of three cores per tree by the Lintab dendrometer with an accuracy of 1 mm. The results show that this species is sensitive mainly to spring precipitation.
Keywords: Pin pignon; dendroécologie.; croissance radiale; cerne; forêt; Akboub; Pinion pinion; dendroecology; radial growth; ring; forest; غابة عرقبوب; النمو الشعاعي; الصنوبر الثمري